Effects of the creative environment on smallholder farmers' skills in rural Colombia - Andrés Alberto Osorio-Londoño; Nixon Cueva-Márquez; Mónica Bibiana González-Calixto (Revista de Investigación, Desarrollo e Innovación)
This study evaluates the effects of the creative environment on smallholder farmers' skills in rural Colombia. To achieve this, a quasi-experimental pre-test and post-test design was employed on a single group of 28 rural smallholder farmers from El Congal Village, in Pensilvania, Caldas, Colombia. Prior to immersion in the creative environment, smallholder farmers were tested on creative skills, and afterwards they were tested again. In order to compare the results of both tests to see whether the intervention was an effective means of improving rural smallholder farmers' creative skills, specially flexibility and fluency, the Wilcoxon rank sum test was used. It was found that the creative environment intervention significantly enhanced both skills. Flexibility measures improved from 8% to 22%, and fluency measures improved from 14% to 49% with the creativity environment intervention. This study suggests that rural smallholder farmers can develop their creative skills through participation in creative environments.